Cerebellar Granule Cell Replenishment Post-Injury by Adaptive Reprogramming of Nestin(+) Progenitors - Wojcinski, Alexandre (Nat Neurosci, 2017)
Regeneration of several organs involves adaptive reprogramming of progenitors, however, the intrinsic capacity of the developing brain to replenish lost cells remains largely unknown. In this study, we discovered that the developing cerebellum has unappreciated progenitor plasticity, since it undergoes near full growth and functional recovery following acute depletion of granule cells, the most plentiful neuron population in the brain. We demonstrate that following postnatal ablation of granule cell progenitors, Nestin-expressing progenitors (NEPs) specified during mid-embryogenesis to produce astroglia and interneurons, switch their fate and generate granule neurons in mice. Moreover, Hedgehog-signaling in two NEP populations is crucial not only for the compensatory replenishment of granule neurons but also to scale interneuron and astrocyte numbers. Thus we provide insights into the mechanisms underlying robustness of circuit formation in the cerebellum, and speculate that adaptive reprogramming of progenitors in other brain regions plays a greater role than appreciated in developmental regeneration.